Performance of herbaceous cotton lines in the state of Alagoas, Brazil - Neto, Miguel Barreiro; Santana, João Cecílio F. de; Neves, Francisco de Paula; Santos, Elton O. dos; Costa, Joaquim N. da; Carvalho, Luis Paulo de; Cavalcanti, Fernando B. (Pesquisa Agropecuaria Brasileira, 2014)
The agronomic performance of new lines of herbaceous cotton (Gossypium hirsutum L.) lines developed by EMBRAPA/Centro Nacional de Pesquisa de Algodão (CNPA) at Campina Grande, PB, Brazil and by other Brazilian research organizations is reported. Observations were made on yield of seed cotton, boll weight, fiber percentage, seed index, fiber length, fineness and strength. The data were obtained from the “Ensaio Regional de Cultivares de Algodoeiro Herbáceo”, which was planted in a randomized complete block design experiment at Delmiro Gouveia, AL, in 1981 and 1982. In the test there were ten lines (seven experimental lines and three cultivars) with eight of the lines evaluated for two years and two varying between years. With regard to seed index, fiber length, fineness and strength, line CNPA 78-SME4, was the most promising, while IAC 17 had the highest boll weight, seed index and percentage of fiber.